Business Ethics in South Africa - Rossouw, G. J. (Journal of business ethics, 1997)
In this paper an assessment will be made of the state of Business Ethics as an academic discipline as well as on the extent to which theory on Business Ethics has been translated into practice within the South African society. First the way in which Business Ethics is defined will be examined. Then the issues within the field of Business Ethics that is considered to be most important will be addressed, as well as the reasons why it is believed to be important to address them. From there the attention will be shifted to the way in which Business Ethics has been institutionalised at tertiary education level. An overview of important initiatives taken by the business sector themselves will also be reviewed. Then co-operation between business and academia on Business Ethics will be discussed. Finally an assessment will be made of what can be learned from Business Ethics elsewhere in the world and what can be offered in this regard. Also some future prospects of Business Ethics in South Africa will be explored.